Die implikasies van die Handves van Menseregte op die pastorale versorging van die homoseksueel - Nagel, Charlene (Hervormde teologiese studies, 1997)
Implications of the Bill of Human Rights for the counceling of homosexuals in the church. Section 8 of the Bill of Human Rigths places the problem surrounding homosexuality on the doorstep of the church. The Bill clearly gives more recognition to the homosexual than in the the past and gives him or her equal standing within society. The Bill implies that the homosexual has the freedom and right to practise his or her sexual preference within a normal society, and this right is protected by law. From a Reformed perspective homosexuality has been deemed unacceptable, in accordance with biblical guidelines, and as therefore not being acceptable within a relationship between the believer and God. Therefore it was naturally considered a duty of the church to council the homosexual towards change. Taking this into account, appdrently the view of the church is in conflict with the Bill of Human Rights. Thus the church has to review its responsibility and duty toward the homosexual in order to play an effective and responsible role in a new society.